2023
DOI: 10.1175/jcli-d-22-0184.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Ocean Circulation and Tropical Atlantic Interannual Modes

Abstract: The impact of tropical Atlantic Ocean variability modes in the variability of the upper-ocean circulation has been investigated. For this purpose, we use three oceanic reanalyses, an interannual forced-ocean simulation, and satellite data for the period 1982–2018. We have explored the changes in the main surface and subsurface ocean currents during the emergence of Atlantic meridional mode (AMM), Atlantic zonal mode (AZM), and AMM–AZM connection. The developing phase of the AMM is associated with a boreal spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(105 reference statements)
2
1
0
Order By: Relevance
“…The downwelling equatorial Kelvin wave that initiated the Atlantic Niño caused a strong reduction of near-surface westward flow close to the equator during May 2021. This is in agreement with a recent study by Martín-Rey et al (2023), who found that the nSEC is weakened during the onset of an Atlantic Niño event. However, while they showed that subsurface currents change little, we observe strengthening and deepening of the Equatorial Undercurrent (EUC) during the onset of the Atlantic Niño from May to June.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The downwelling equatorial Kelvin wave that initiated the Atlantic Niño caused a strong reduction of near-surface westward flow close to the equator during May 2021. This is in agreement with a recent study by Martín-Rey et al (2023), who found that the nSEC is weakened during the onset of an Atlantic Niño event. However, while they showed that subsurface currents change little, we observe strengthening and deepening of the Equatorial Undercurrent (EUC) during the onset of the Atlantic Niño from May to June.…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with a recent study by Martín‐Rey et al. (2023), who found that the nSEC is weakened during the onset of an Atlantic Niño event. However, while they showed that subsurface currents change little, we observe strengthening and deepening of the Equatorial Undercurrent (EUC) during the onset of the Atlantic Niño from May to June.…”
Section: Discussionsupporting
confidence: 94%
“…The tropical Atlantic Ocean plays an important role in the global climate system as it is a gateway for the northward branch of the Atlantic Meridional Overturning Circulation (AMOC) that transports warm water from the South to the North Atlantic (Martín-Rey et al, 2023;Schott et al, 2004;Tuchen et al, 2022b). Additionally, the subtropical and tropical Atlantic are connected via shallow meridional overturning cells, so-called subtropical cells (STCs) (Liu et al, 1994;McCreary & Lu, 1994;Schott et al, 2004).…”
Section: Introductionmentioning
confidence: 99%